Biomarkers for noninvasive biochemical diagnosis of nonalcoholic steatohepatitis: Tools or decorations? - YILMAZ, YUSUF (W J G PRESS, 2009)
In light of the growing epidemics of nonalcoholic fatty liver disease (NAFLD), identification and validation of the novel biochemical surrogate markers for nonalcoholic steatohepatitis (NASH) are paramount to reduce the necessity for liver biopsy. The availability of such markers has tremendous potential to radically alter the management strategies of NAFLD patients and to monitor the disease activity. Although current biomarkers do not entirely fulfill the many requirements for the identification of patients with NASH, they should not discourage our quest, but remind us that we need to cognize the challenges ahead. (C) 2009 The WJG Press and Baishideng. All rights reserved.
Keywords: Nonalcoholic fatty liver disease; Nonalcoholic steatohepatitis; Biomarkers; Liver biopsy; FATTY LIVER-DISEASE; VALUES